2002
DOI: 10.1093/humrep/17.6.1447
|View full text |Cite
|
Sign up to set email alerts
|

Human ovarian tissue cryopreservation: indications and feasibility

Abstract: Cryopreservation of ovarian tissue may be systematically proposed to young women and girls at risk of becoming sterile as a result of gonadotoxic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
87
3

Year Published

2005
2005
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(101 citation statements)
references
References 25 publications
7
87
3
Order By: Relevance
“…45,50,51 Because of their large size, water content, and chromosomal architecture, mature female oocytes are extremely fragile. The spindle apparatus of the chromosome is easily damaged by intracellular ice formation during the freezing or thawing process.…”
Section: Femalesmentioning
confidence: 99%
See 1 more Smart Citation
“…45,50,51 Because of their large size, water content, and chromosomal architecture, mature female oocytes are extremely fragile. The spindle apparatus of the chromosome is easily damaged by intracellular ice formation during the freezing or thawing process.…”
Section: Femalesmentioning
confidence: 99%
“…45 Within this context, it is the only method that can be offered to prepubertal girls. 50 There are a large number of immature oocytes in the ovarian cortex at this age, when the primordial follicles contain prophase I oocytes. This technique has been accomplished in children as young as 2.7 years of age, and the chance of later restoring fertility should be higher, theoretically, because the ovarian cor-tex contains an increased number of primordial and primary follicles in younger children.…”
Section: Femalesmentioning
confidence: 99%
“…In this series, two patients had chemotherapy prior to cryopreservation, the first, and one of the women with systemic lupus erythematosis (SLE) who had previously received some cyclophosphamide. Others have argued that cryopreservation after chemotherapy may be appropriate (Poirot et al 2002, Meirow et al 2007, although the health of oocytes/follicles cryopreserved under those conditions is uncertain and may increase the risk to a subsequent pregnancy due to the DNA-damaging mechanism of action of some chemotherapeutic agents. A recent study has demonstrated increased oocyte vacuolisation and granulosa cell nuclear abnormalities after chemotherapy (Abir et al 2008), supporting the practice of confining cryopreservation to before treatment.…”
Section: Patient Outcomesmentioning
confidence: 99%
“…Many have proposed unilateral oophorectomy, and this has been the method used in some reports , Poirot et al 2002, Schmidt et al 2005, Andersen et al 2008. We have generally avoided this, other than in the case of our youngest patient who was to receive chemotherapy and pelvic radiotherapy.…”
Section: Patient Outcomesmentioning
confidence: 99%
See 1 more Smart Citation